María Eugenia MATÍA AMOR, "Las dimensiones de la memoria. La poesía de Arcadio Pardo". Valladolid, Universidad de Valladolid, 2018, 260 pp. - Ayuso, César Augusto (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
This paper is a review of the book: The Dimensions of the Memory: The Poetry of Arcardio Pardo. Author: María Eugenia MATÍA AMOR Valladolid, Universidad de Valladolid, 2018, 260 pp.